ETHICAL DILEMMAS IN NEUROMARKETING: NAVIGATING PERSUASION, CONSUMER AUTONOMY, AND EMERGING TECHNOLOGIES - Muhamad Stiadi; Luana Sasabone; Deisye Supit; Cut Ita Erliana; Dahlan Abdullah (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2024)
Neuromarketing is a rapidly growing field that uses neuroscience to understand consumer behavior and improve marketing effectiveness. This article explores the complex ethical implications of neuromarketing practices, especially regarding persuasive influence on consumer autonomy and the use of emerging technologies. First, we investigate advances in neurotechnology, such as fMRI, EEG, and brain-computer interfaces (BCIs), that enable a deeper understanding of consumer preferences. The challenge is enforcing this technology's ethical use and protecting individual privacy. Second, we discuss "neuro hacking," exploiting neurological vulnerabilities to influence consumer decisions. This raises ethical questions about mental safety and individual autonomy. Third, algorithms and artificial intelligence in Neuromarketing create highly personalized marketing experiences. This raises questions about how to protect privacy, obtain consent, and maintain individual agency. Fourth, we explore cultural issues in Neuromarketing, exploring how cultural values must be respected in marketing practices. Fifth, we discuss security and data protection issues in using neuromarketing technology. Sixth, we investigate the role of government and regulatory agencies in regulating neuromarketing practices and protecting consumer rights. Finally, we highlight the importance of education about neuroethics in educating marketers, researchers, and consumers about the ethical aspects of Neuromarketing. This article encourages critical reflection on the ethical dilemmas businesses, researchers, and policymakers face in the rapidly evolving world of Neuromarketing.